Potential Study of Hazardous Waste Sludge Recycle for Substituting the Supporting Raw Material in Fertilizer Manufacturing - Awidi, Saraswati Sinti; Temmy Wikaningrum (Jurnal Serambi Engineering, 2025)
Waste water treatment facilities (WWTP) are producing a rising amount of sludge, which poses serious disposal and environmental issues. The purpose of this study is to investigate the possibility of using WWTP sludge in place of filler materials while making NPK fertilizer. Significant levels of vital elements, including nitrogen (N), phosphorous (P), and potassium (K), which are crucial for fertilizer quality, were found in the sludge after a thorough physical and chemical analysis. A comparative assessment was performed between the WWTP sludge and standard clay filler materials to evaluate compliance with Indonesian National Standard (SNI) 2803:2024 for solid NPK fertilizers. Experimental mixing trials identified the optimal sludge-to-clay ratio as 60:40, which produced fertilizer granules with acceptable physical properties, homogeneity, and nutrient content that met the SNI requirements. This study shows that using WWTP sludge as a filler in fertilizer manufacture has major financial advantages in addition to supporting resource recovery and sustainable waste management. The study promotes the use of sewage reuse in fertilizer production as a creative way to solve environmental issues and boost industrial productivity.